Attitudes, beliefs and behaviour towards shoulder injury prevention in elite handball: Fertile ground for implementation - Haugsboe Andersson, S.; Bahr, R.; Johnsen Olsen, M.; Myklebust, G. (Scandinavian Journal of Medicine & Science in Sports, 2019)
We aimed to examine attitudes, beliefs and current behaviour towards risk factors and prevention of shoulder injuries, and to investigate the application of an exercise programme during a cluster-randomised controlled trial aiming to prevent shoulder injuries in elite handball. All captains and coaches of 44 elite handball teams (22 male, 22 female) constituting the intervention (21 teams) and control arm (n=23 teams) in the trial were invited to take part in a survey. A questionnaire, based on the Reach, Efficacy, Adoption, Implementation and Maintenance framework, addressing the end-user perspective on risk factors and prevention of shoulder injuries, as well as key issues related to the application of the Oslo Sports Trauma Research Center (OSTRC) Shoulder Injury Prevention Programme, was distributed using electronic survey software. The response rate was 100%. Overall, the majority of coaches (84%) and captains (89%) believed that handball players are at high risk for shoulder injuries. All delivery agents in the trial reported to be familiar with the exercise programme and the majority believed in a preventative effect (coaches 90%, captains 81%). Only a minority reported full compliance with the recommended frequency (coaches 29%, captains 14%), with programme being too time consuming (coaches 67%, captains 81%) and lack of player motivation (coaches 76%, captains 62%) as the main barriers. Our results suggest that there is fertile ground for implementation of the OSTRC Shoulder Injury Prevention Programme in elite handball, with programme length and lack of player motivation as the main barriers to overcome.